1992
DOI: 10.1007/bf01923441
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the extranuclear localization of thymosins in thymus

Abstract: A new radioimmunoassay has been developed for thymosin beta 4 by generating rabbit polyclonal antibodies against the synthetic N-terminal peptide fragment 1-15 coupled to KLH. The synthetic analogue [Tyr12]-thymosin beta 4 (1-15) was used as tracer. This radioimmunoassay, with a useful range of 10-1000 pmoles, showed cross-reactivity with the second homologous beta-thymosin of man and rat (thymosin beta 10) but not of calf (thymosin beta 9). This radioimmunoassay, together with an improved radioimmunoassay for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
5

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
8
0
5
Order By: Relevance
“…On the other hand, Tsitsiloni et al (21) found an extranuclear localization of ParaT in thymus by radioimmunoassay and we have previously reported, by light immunohistochemical procedures, the cytoplasmic localization of ParaT in the reticuloepithelial cells of the rat thymus (16). Similarly, Brand et al (2) found immunostaining for ParaT exclusively in the cytoplasm of most cell types that they studied, including hepatocytes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…On the other hand, Tsitsiloni et al (21) found an extranuclear localization of ParaT in thymus by radioimmunoassay and we have previously reported, by light immunohistochemical procedures, the cytoplasmic localization of ParaT in the reticuloepithelial cells of the rat thymus (16). Similarly, Brand et al (2) found immunostaining for ParaT exclusively in the cytoplasm of most cell types that they studied, including hepatocytes.…”
Section: Discussionsupporting
confidence: 66%
“…However, the main physiological function of ParaT has not been found (2). Its intracellular localization is also controversial and both a nuclear (2,6,22) and a cytoplasmic distribution (3,16,21) have been proposed. The aim of the present work was to determine, by light immunohistochemical and immunogold labelling procedures, the subcellular distribution of ParaT in rat and human hepatocytes.…”
mentioning
confidence: 99%
“…β-Thymosins contain highly conserved acidic 5 kDa peptides consisting of 40-44 amino acid residues, of which 50% are charged (4,5). To date, there are at least 15 β-thymosins identified in species ranging from various invertebrates to vertebrates (2,6), and they are thought to be localized in either the nucleus or cytoplasm (7,8) and can interact with monomeric G-actins (9)(10)(11). The first β-thymosin peptide isolated was thymosin β1 (Tβ1) (12).…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years it has been found that their distribution is not limited to the thymus but that they are also present in numerous tissues [5,6]. Recent experiments provided evidence for their extranuclear localization in the cells [7]. Different b-thymosin peptides have been isolated from many species of the animal kingdom, ranging from amphibia to mammals [8±15].…”
Section: Introductionmentioning
confidence: 99%